STRATEGI DAN SISTEM PEMASARAN IKAN DI PANGKALAN PENDARATAN IKAN (PPI) BEBA KABUPATEN TAKALAR - Andi Teti; Danial Danial; Ihsan Ihsan (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
Pendaratan Pendaratan Ikan (PPI) Beba is one of the most crowded Fish Port landing and fish market in Takalar Regency. The high trading volume and marketing of fish at PPI Beba has caused the need for an assessment of marketing efficiency to determine the effectiveness of fish marketing at the PPI Beba so that a Marketing strategy can be arranged that is suitable with the conditions of fish marketing in the PPI Beba. This research was conducted from September to October 2018, using primary data and secondary data. The aim of this research are formulating fish marketing strategies at the PPI Beba North Galesong District Takalar Regency. Data analysis was carried out in several stages, namely by conducting namely by analyzing the margins anddistribution of marketing, analyzing marketing effectiveness and then conducting the S.W.O.T analysis method (Strengthen, Weakness, Opportunities, and Threats) show that marketing margins were still more enjoyed by retailers and collectors than those received by fishermen. In addition, the analysis showed that the marketing efficiency of fish at PPI was still quite low. The results of analysis using the SWOT method show the marketing strategy of fisheries production at PPI It is necessary to pay attention to faktors that are significant to the condition of the PPI, activation of auction (TPI), develop marketing facilities and infrastructure, develop market access, modernize tools and fishing vessels, determine pricing, capital capabilities, knowledge of fishermen ranging from preproduction, processing to marketing to improve the welfare of fishermen.